Endophytic Bacteria Producing Alkaloid as Antibacterial and Antioxidant Agent from Hibiscus tiliaceus Leaves - Purbowatiningrum Ria Sarjono; Aulia Anggraeni; Ismiyarto Ismiyarto; Ngadiwiyana Ngadiwiyana (Jurnal Kimia Sains dan Aplikasi, 2024)
Hibiscus tiliaceus is known to have antibacterial activity. One of the antibacterial compounds contained in the hibiscus plant is alkaloid. Alkaloids can also be obtained from endophytic bacteria that are in symbiosis with hibiscus leaves. It is known that endophytes can produce the same or similar secondary metabolites as their host plants. Medicinal plants have been proven to be a source of microorganisms that can make certain metabolites. Our previous research succeeded in isolating the endophytic bacteria Staphylococcus warneri strain 25 from waru leaves (Hibiscus tiliaceus), which had antioxidant and antibacterial activity and contained saponins and alkaloids. In this study, alkaloids were extracted from the endophytic bacteria found in waru leaves. Subsequently, their bioactivity was assessed for antibacterial properties against Escherichia coli, Salmonella typhi, and Staphylococcus aureus using the well diffusion method. Additionally, their antioxidant activity was evaluated through the DPPH method, with gallic acid serving as the standard. A cyclic amine alkaloid compound was isolated, exhibiting a Minimum Inhibitory Concentration (MIC) of 23 ppm against E. coli, S. typhi, and S. aureus bacteria, accompanied by inhibitory zones measuring 7 mm, 8 mm, and 6 mm, respectively. Additionally, the compound had very strong antioxidant activity, with an IC50 value of 50.11 ppm.